The diaspora of Brazilian religions - Rocha, Cristina; Vásquez, Manuel A. (International studies in religion and society ;, 2013)
This book explores the global spread of religions originating in Brazil, a country that has emerged as a major pole of religious innovation and production. Through ethnographically-rich case studies throughout the world, ranging from the Americas (Canada, the U.S., Peru, and Argentina) and Europe (the U.K., Portugal, and the Netherlands) to Asia (Japan) and Oceania (Australia), the book examines the conditions, actors, and media that have made possible the worldwide construction, circulation, and consumption of Brazilian religious identities, practices, and lifestyles, including those connected with indigenized forms of Pentecostalism and Catholicism, African-based religions such as Candomblé and Umbanda, as well as diverse expressions of New Age Spiritism and Ayahuasca-centered neo-shamanism like Vale do Amanhecer and Santo Daime.